ICT USAGE IN PRIMARY SCHOOL LESSONS - Pavlenko , Vita (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article discusses the effectiveness of ICT (Information and Communication Technologies) usage in primary school lessons. Two types of ICT tools used in the education system are analyzed: hardware and software. The advantages and disadvantages of ICT implementation in the educational process are identified.